Parents’ Experience of the Transition with their Child from a Pediatric Intensive Care Unit (PICU) to the Hospital Ward: Searching for Comfort Across Transitions - Berube, Kristyn M. (Université d'Ottawa / University of Ottawa, 2013)
The pediatric intensive care unit (PICU) has been described as a stressful place for parents of critically ill children. Research to date has examined parents’ needs and stressors with a child in PICU. There is a paucity of research examining the experience for parents of a child who is transferred from the PICU to the hospital ward. Open-ended interviews were conducted with 10 parents within 24-48 hours after transfer from a PICU to a hospital ward at a children’s hospital in Canada to understand this experience. Parents revealed that the experience involved a search for comfort through transitions as expressed through the themes of: ‘being a parent with a critically ill child is exhausting’, ‘being kept in the know’, ‘feeling supported by others’, and ‘being transferred’. The findings from this study can help nurses and other health professionals working with parents to support them through the transition from PICU. Recommendations are made for the inclusion of family-centered care practices to assist parents through transitions.
Keywords: Phenomenology; Pediatrics; Pediatric Intensive Care Unit; Transition; Parents; Parental experience